Statistical analysis of decathlon: A new approach - Ciacci, S.; Passarelli, A.; Merni, F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Decathlon is one of the most challenging disciplines in track and field. Previous studies have assessed the relationships between the performance in the 10 decathlon events by means of correlations or cluster analyses (Woolf et al, 2007, Cox et al, 2002, Van Damme et al, 2000). The aim of this study was to assess the correlations between the 10 decathlon events and the final competitive outcome, with particular focus on possible strategies used to achieve the final score by athletes of the most represented nations in the top 100 all-time world ranking. Methods: The 100 world top (all-time) decathlon performances (taken from IAAF scores) were analysed. Scores achieved before the change of the javelin throw rule in 1986, have been compared to the results obtained after 1986, after standardization of the different throwing results according to Borgström (2000). The ranking has been analyzed to investigate how the different events are clustered and affect the final score. Furthermore, the data of the 3 states with the highest number of athletes in the all-time list (Russia, Germany and USA) were compared to study how their training strategies may affect the final performance. Results: In agreement with previous studies (Cox et al, 2002, Woolf et al, 2007), the analysis showed two main clusters observed in the dendrograms. The 100m, 110m hurdles and long jump belonged to the same cluster and their scores were well correlated with the final results (r between 0.536 and 0.564). The shot put and discus throw were linked to another cluster, and were not correlated with the final score. The javelin throw, the pole vault and the high jump showed a weaker relationship with the final score, probably due to the high level of technical skill required. There were no significant differences between the three examined nations , with the exception of the average 100m and 1500m results between Russia and USA (851 pts vs. 892pts, and 745 pts vs. 702 pts, respectively). Discussion: The results show that the sprint events influence the decathlon performance more than other events. This outcome may be taken into account to select talents and develop a more effective training programs. Among the 3 examined nations, USA showed higher score than the Russia especially in the sprint events and consequently in the final score. Russia showed better scores in the throwing events and 1500m race. Finally, athletes from Germany were generally ranked between those of the other 2 nations in all the decathlon events.